STUDY OF THE QUALITY AND SAFETY OF BLACK TEA WITH BERGAMOT - RATSUK, MARIIA; YUROVA TAТYANA; RATSUK, KATERYNA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Tea is one of the most popular beverages in the world, with consumption spanning millions of people and cultures. Many Ukrainians prefer this drink to coffee, especially during the cold season. Black tea can have a positive effect on the body due to its content of antioxidants, vitamins and other nutrients. In particular, catechins in black tea have antiviral and antimicrobial properties, helping to fight infections. Antioxidants protect blood vessels and the heart from damage. Tannins in black tea help maintain the balance of microflora in the intestines. And this is not a complete list of the beneficial properties of tea for the human body. The modern tea market is undergoing significant changes due to new trends and innovations. The growing interest in healthy lifestyles and natural products is contributing to the popularity of local producers who strive to meet the needs of conscious consumers. Many brands are starting to offer flavored teas, and bergamot tea is very popular among them. We can safely say that bergamot tea is a healthy and very recognizable tea. The finished drink has a delicate aroma and unique taste with notes of citrus. There is a wide range of bergamot tea on the modern market, so there is a need to assess the quality and safety of this drink. The organoleptic characteristics and labeling of black tea flavored with bergamot of different brands were evaluated. It was determined that the studied tea samples meet the requirements of regulatory documents according to the established criteria. The raw materials and technological process of production of black tea flavored with bergamot were analyzed, which made it possible to identify hazards and develop elements of the HACCP plan.